Editorial: El estado como agente de cambio social en América Latina - RBEUR, Comissão Editorial; García, Ariel; Silveira, Rogério Leandro Lima da; Schweitzer, Mariana; Manríquez, Marcel Theza; Bertoni, Reto (Revista Brasileira de Estudos Urbanos e Regionais, 2023)
não se aplica